Metode Penulisan Artikel Telaah Literatur - Anung Ahadi Pradana; Muhammad Chandra; Ismail Fahmi; Casman; Alfunnafi' Fahrul Rizzal; Nani Asna Dewi; Nur’aini (Fakultas Ilmu Kesehatan Universitas Dharmas Indonesia, 2021)
Lecturers in Indonesia only focus on original research in implementing Tri Dharma of Higher Education. A literature review has not been optimally used because of the lack of guidance. This article aimed to describe what a literature review is and how to compile good literature. This article is a simple literature review. The keywords used were